Bulbostylis litoreamazonicola, a new species of Cyperaceae from the Brazilian Amazonian coast - Maciel-Silva, Juliene De Fátima; Prata, Ana Paula Do Nascimento; López, Maria Gabriela; Gil, André Dos Santos Bragança (Phytotaxa, 2022)
A new species of Bulbostylis (Cyperaceae), only known from the Brazilian Amazonian coast, is here described and illustrated. Bulbostylis litoreamazonicola was found growing over dunes, in seasonally flooded restinga vegetation, and in humid fields near the mangroves from the State of Pará, Northern Brazil. This is the fifth Brazilian-native species of Bulbostylis lacking a persistent stylopodium on the mature fruit. The new species is mainly characterized by its annual habit, simple anthelate inflorescences, densely hispid to hispidulous longitudinally ribbed scapes, pubescent glumes, and cordiform nutlets.